Analysis of supplier selection criteria using fuzzy analytical hierarchy process by contractors in Yogyakarta - Tiblola, Lidya Iriani Thabita; Aminullah, Akhmad; Nugroho, Arief Setiawan Budi (Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
One of the factors that can support the success of a project to be completed on time and within budget is the selection of the right supplier because the selection of the right supplier can ensure the availability of materials to maintain the production trajectory. Supplier selection is a multi-criteria problem where each criterion has a different importance and needs to be precisely known. It must combine other criteria consistent with company goals to achieve maximum supply chain performance. Therefore, it is necessary to evaluate the supplier performance criteria needed by each company. The purpose of this research is to prioritize factors that contractors can use in selecting suppliers so that construction entrepreneurs can determine which suppliers can perform from the best criteria. One supplier selection method is the Analytic Hierarchy Process (AHP) method. However, this method still has a problem in the form of subjective assessment results, thus requiring a method that can overcome these problems, namely the Fuzzy Analytic Hierarchy Process method. Based on the literature study results, this research identifies 18 factors that influence the selection of material suppliers, which are grouped into six categories: Delivery, quality, price, service, performance, and management. Data collection in this study used questionnaires distributed to 10 respondents and processed using the Fuzzy AHP method. Based on the data processing that has been done, it is obtained that the criteria that prioritize local contractors in Yogyakarta in selecting suppliers are quality criteria with a value of 0,380, followed by cost criteria with a value of 0,283, and delivery criteria with a value of 0,157.